Study Of Energy Efficient And Secure Routing Mechanisms In Wireless Sensor Network - et. al., C. Nithya Praba, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Sensor Network (WSN) is a group of Sensor Nodes (SN) correspond with each other and sharing the information between the networks. SN are low power and low cost devices are used to construct the network. Sensor based networks are used in various integrated applications. One of the most benefited sensor based application is Healthcare applications. In Healthcare applications, the physical components are data sources and collected information’s are transmitted through the network in the mode of intermediate node access. All the physical components or sensors are battery powered in nature, so the energy was play a vital role in Healthcare-WSN (HWSN) applications. Nodes energy will decide the utilisation of the network and accurate data transmission between the nodes. The future of WSN is purely dependent on the Energy saving mechanism and now it is create a new dimension of research constraint. Now, the researchers focusing on the Energy efficient and secure techniques for improve the lifetime of the network and safest data transmission between the nodes and the server. In this paper, various energy efficient mechanisms are analyzed for prolong the network and also review the various secure mechanisms to improve the security of the HWSN applications.